Does combined pulmonary fibrosis and emphysema syndrome affect response to antifibrotic therapy and survival? A single-center retrospective cohort study - Teke, Nazli Huma; Agca, Meltem; Turkar, Ayla; Sevim, Tülin; Tuncay, Eylem; Gungor, Sinem; Yıldırım, Elif; Ozbaki, Fatma; Gundogus, Baran; Arınc, Sibel; Berk Takır, Huriye; Ozmen, Ipek (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Objective: Combined pulmonary fibrosis and emphysema (CPFE) is a clinicoradiological syndrome characterized by upper lobe emphysema and lower lobe fibrosis, most commonly associated with idiopathic pulmonary fibrosis (IPF). This study compared the clinical characteristics, functional parameters, and mortality of patients with CPFE and IPF who received antifibrotic therapy.Methods: Between October 2015 and August 2022, patients with IPF treated with antifibrotics for at least 6 months were retrospectively evaluated and divided into two groups: CPFE (emphysema present) and IPF (emphysema absent). Demographic data, antifibrotic therapy, functional parameters before and after treatment (FEV1%, FVC%, DLco %), clinical outcomes (hospital admissions, mortality) were compared.Results: Of the 204 patients with IPF, 90 (44%) had CPFE. CPFE patients were more often male, had greater smoking history, higher pack-years, and more lung cancer than IPF patients (p < 0.001 for all). Post-treatment FEV1% and FVC% did not significantly differ between the groups, whereas DLco% declined significantly in both (p < 0.001 and p = 0.002). DLco% decreased more in IPF than CPFE, but the difference was not statistically significant [−3 (−11–3) vs. −0.43 (−1.1–0.2), p = 0.36]. The hospital admission rates were similar. Independent risk factors for mortality included CPFE diagnosis (HR: 1.73, 95% CI: 1.06–2.83, p = 0.029), low FVC% (HR: 0.970, 95% CI: 0.96–0.98, p < 0.001), and device use (long-term oxygen therapy [LTOT]  or home non-invasive mechanical ventilation [NIMV]) (HR: 2.48, 95% CI: 1.50–4.09, p < 0.001). Mean survival was shorter in patients with emphysema than in those without emphysema (5.08 vs. 5.68 years, p = 0.08).Conclusions: Despite a decline in DLco%, changes remained below the futility threshold. Clinical outcomes and mortality were comparable. CPFE diagnosis, low FVC%, and LTOT/NIMV use independently predicted higher mortality.